Reovirus-directed Ribonucleic Acid Synthesis in Infected L Cells - Shatkin, A. J. (1967)
Reovirus replication in L-929 mouse fibroblasts was unaffected by 0.5 μg of actinomycin per ml, a concentration which inhibited cell ribonucleic acid (RNA) synthesis by more than 90%. Under these conditions of selective inhibition, the formation of both single-stranded and double-stranded virus-specific RNA was detected beginning at 6 hr after infection. The purified double-stranded RNA was similar in size and base composition to virus RNA and presumably was incorporated into mature virus. The single-stranded RNA formed ribonuclease-resistant duplexes when annealed with denatured virus RNA but did not self-anneal, thus indicating that it includes copies of only one strand of the duplex. The single-stranded RNA was polyribosome-associated and may function as the virus messenger RNA. Production of both types of virus-induced RNA required protein synthesis 6 to 9 hr after infection. At later times in the infectious cycle, only double-stranded RNA synthesis was dependent on continued protein formation.